The invention of the papacy (2019)
This thesis has two main aims. The first is to examine the intellectual development of the later ninth-century papacy in its Roman context, including its engagement with the outside world and the remarkable levels of ‘papal myth-making’ prevalent in later ninth-century Rome. It examines the careers of some of the key figures in this ‘myth-making’, namely Anastasius Bibliothecarius, John the Deacon, Gauderic of Velletri and Formosus, and investigates the linkages between this ‘myth- making’ process and the papacy’s involvement with the outside world. It also briefly charts the decline of this remarkably lively and energetic intellectual culture, and looks at Rome’s descent into aristocratic in-fighting at the end of the end of the ninth and beginning of the tenth centuries, symbolised most obviously by the disputes over the papacy of Formosus and the legitimacy or otherwise of episcopal transfer.